A New Year of Catalysts - Hohn, Keith L. (My University, 2016)
Excerpt: Welcome to a new year of Catalysts, an international, peer-reviewed open access journal. From time to time, I like to write about the status of the journal: what milestones have been reached, what special issues will be coming out, what conferences we will partner with, etc. As we turn to the New Year, this seems like an opportune time to provide an update on Catalysts.
Citation: Hohn, K. L. (2016). A New Year of Catalysts. Catalysts, 6(1), 2. doi:10.3390/catal6010016
Keywords: Chemistry